Effect of nano/micro‐mixed ceramic fillers on the dielectric and thermal properties of epoxy polymer composites. (13th November 2013) - Vaisakh, S. S.; Hassanzadeh, Mehrad; Metz, Renaud; Ramakrishnan, S.; Chappelle, Delphine; Sudha, J. D.; Ananthakumar, S.
<x xml:space="preserve">Abstract</x> Nano/micro ceramic‐filled epoxy composite materials have been processed with various percentage additions of SiO2, Al2O3 ceramic fillers as reinforcements selected from the nano and micro origin sources. Different types of filler combinations, viz. only nano, only micro, nano/micro, and micro/micro particles, were designed to investigate their influence on the thermal expansion, thermal conductivity, and dielectric properties of epoxy polymers. Thermal expansion studies were conducted using thermomechanical analysis that revealed a two‐step expansion pattern consecutively before and after vitreous transition temperatures. The presence of micro fillers have shown vitreous transition temperature in the range 70–80°C compared with that of nano structured composites in which the same was observed as ~90°C. Similarly, the bulk thermal conductivity is found to increase with increasing percentage of micron‐size Al2O3. It was established that the addition of micro fillers lead to epoxy composite materials that exhibited lower thermal expansion and higher thermal conductivity compared with nano fillers. Moreover, nano fillers have a significantly decisive role in having low bulk dielectric permittivity. In this study, epoxy composites with a thermal expansion coefficient of 2.5 × 10−5/K, thermal conductivity of 1.18 W/m · K and dielectric permittivity in the range 4–5 at 1 kHz have been obtained. The study confirms that although the micro fillers seem to exhibit good thermal conductivity and low expansion coefficient, the nano‐size ceramic fillers are candidate as cofillers for low dielectric permittivity. However, a suitable proportion of nano/micro‐mixed fillers is necessary for achieving epoxy composites with promising thermal conductivity, controlled coefficient of thermal expansion and dielectric permittivity. Copyright © 2013 John Wiley & Sons, Ltd.